Peningkatan Kesiapan Kerja Melalui Pelatihan Efikasi Diri dalam Bidang Pekerjaan pada Calon Tenaga Kerja - Tekad Wahyono (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2004)
The aim of this research is to examine the effectiveness of occupational self-efficacy training in improving work readiness among work applicants. The proposed hypothetis is: there is a work readiness differences between a group where the occupational self-efficacy training is given and  a group without self efficacy training.  A group given occupational self-efficacy training shows  higher work readiness.Subjects were 42 people and were divided into two groups (experimental group and control group) at random. The research applies the pretest posttest control group design. Data were collected from work readiness scale and analyzed by one way anova.The result of the analysis indicates that F (between groups) = 65.142,  p = 0.000 (pKey words: occupational self-efficacy training, work readiness